An evaluation of inflation expectations in Turkey - Baris Soybilgen; Ege Yazgan (Central Bank Review (CBR), 2017)
Expectations of inflation play a critical role in the process of price setting in the market. Central banks closely follow developments in inflation expectations to implement a successful monetary policy. The Central Bank of the Republic of Turkey (CBRT) conducts a survey of experts and decision makers in the financial and real sectors to reveal market expectations and predictions of current and future inflation. The survey is conducted every month. This paper examines the accuracy of these survey predictions using forecast evaluation techniques. We focus on both point and sign accuracy of the predictions. Although point predictions from CBRT surveys are compared with those of autoregressive models, sign predictions are evaluated on their value to a user. We also test the predictions for bias. Unlike the empirical evidence from other economies, our results show that autoregressive models outperform most of inflation expectations in forecasting inflation. This indicates that inflation expectations have poor point forecast accuracies. However, we show that sign predictions for all inflation expectations have value to a user.
Keywords: 330; Inflation expectations; Evaluation procedures; Sign forecast accuracy